Immune checkpoints in the tumor microenvironment. (October 2020) - Toor, Salman M.; Sasidharan Nair, Varun; Decock, Julie; Elkord, Eyad
Abstract: Interactions between immune checkpoints (ICs) and their ligands negatively regulate T cell activation pathways involved in physiological immune responses against specific antigens. ICs and their ligands are frequently upregulated in the tumor microenvironment (TME) of various malignancies, and they represent significant barriers for induction of effective anti-tumor immune responses. Several IC inhibitors (ICIs) have been developed, with some currently in clinical trials and others have been approved for the treatment of different cancers. However, tumor cells are able to counteract the activity of ICIs and can commission additional inhibitory pathways via expression of other ICs/ligands within the TME. This review discusses the expression of various ICs/ligands in the TME and their impact on tumor immune evasion. Additionally, we discuss various regulatory mechanisms, including genetic and epigenetic, and other modulatory factors including hypoxia and the presence of immunosuppressive populations in the TME, which result in upregulation of ICs in various cancers. Moreover, we discuss the prognostic significance of ICs and their ligands, and the potential strategies to enhance treatment responses to ICIs. This review aims to advance our current knowledge on the role of ICs in the TME and the clinical benefits of targeting them.